Clinical Analysis of the Discovery of Malignant Gynecological Tumors in the Diagnosis and Treatment of Pelvic Organ Prolapse - Niu, Li-Na; Wang, Jun-Xia; Li, Xia; Xu, Yong-Jun; Qiu, Li-Rong; Guo, Sheng; Zhang, Li-Zhen; Shang, Yun (Frontiers in Surgery, 2022)
Background: Clinically, malignant gynecological tumors found by chance during the diagnosis and treatment of pelvic organ prolapse (POP) are rare, and they are usually missed, leading to delayed diagnosis and treatment. The initial treatment of these tumors cannot be standardized, and, as a single surgical intervention may not be able to treat both the tumor and prolapse, secondary surgery is usually needed, affecting the quality of life of patients. Case presentation: The present study retrospectively analyzed the data of three patients who were diagnosed with malignant gynecological tumors during the diagnosis and treatment of POP. These patients were among 215 patients with POP treated in Yuncheng Central Hospital of Shanxi Province between January 2011 and May 2020. The case characteristics, surgical interventions, postoperative treatments, and follow-ups were summarized, and the characteristics of diagnosis and treatment were analyzed in the context of relevant literature. Conclusion: As long as clinicians operate in strict accordance with the standards of diagnosis and treatment, obtain a complete medical history, undertake a physical examination, and remain diligent in auxiliary examinations, following existing clinical methods and diagnosis and treatment processes, patients with POP complicated with malignant gynecological tumors can be clearly diagnosed before and during surgery. In this way, initial treatment can be standardized, and surgical methods can be selected that address both the tumor and prolapse, thereby avoiding secondary surgery and improving the patient’s quality of life.